Magnetic Resonance Angiography of Intracranial Aneurysms: Comparison with Intra-arterial Digital Subtraction Angiography - R Basiratnia (Journal of Research in Medical Sciences, 2004)
Background: The aim of this study is to determine sensitivity and specificity of 3D- Time-Of-Flight and Phase Contrast Magnetic resonance angiography (MRA) in comparison with intra-arterial digital subtraction angiography (IA- DSA) in detection of intracranial aneurysms. Methods: 54 patients with 22 aneurysms underwent MRA and then IA-DSA prospectively from October 2002 till December 2003. Results: MRA detected 20 aneurysm where as IA- DSA scored 22 (90.9%). false positive in MRA was 18.1% (4 cases) and no false positive was in IA- DSA. So sensitivity of MRA in detection of intracranial aneurysms is 90.9%, and specificity is 88.8%. Positive predictive value of 83.3% and negative predictive value of 94.1% is also calculated. Conclusion: MRA is a valuable non- invasive technique in the detection of intracranial aneurysms that can be a proper screening test for this purpose. Keywords: MRA, IA- DSA, Aneurysm.